Glycogen Synthase Kinase-3 in the Etiology and Treatment of Mood Disorders - Jope, Richard S. (Frontiers in Molecular Neuroscience, 2011)
The mood disorders major depressive disorder and bipolar disorder are prevalent, are inadequately treated, and little is known about their etiologies. A better understanding of the causes of mood disorders would benefit from improved animal models of mood disorders, which now rely on behavioral measurements. This review considers the limitations in relating measures of rodent behaviors to mood disorders, and the evidence from behavioral assessments indicating that glycogen synthase kinase-3 (GSK3) dysregulation promotes mood disorders and is a potential target for treating mood disorders. The classical mood stabilizer lithium was identified by studying animal behaviors and later was discovered to be an inhibitor of GSK3. Several mood-relevant behavioral effects of lithium in rodents have been identified, and most have now been shown to be due to its inhibition of GSK3. An extensive variety of pharmacological and molecular approaches for manipulating GSK3 are discussed, the results of which strongly support the proposal that inhibition of GSK3 reduces both depression-like and manic-like behaviors. Studies in human postmortem brain and peripheral cells also have identified correlations between alterations in GSK3 and mood disorders. Evidence is reviewed that depression may be associated with impaired inhibitory control of GSK3, and mania by hyper-stimulation of GSK3. Taken together, these studies provide substantial support for the hypothesis that inhibition of GSK3 activity is therapeutic for mood disorders. Future research should identify the causes of dysregulated GSK3 in mood disorders and the actions of GSK3 that contribute to these diseases.